Pengaruh Pemberitaan Bencana Alam di Harian Serambi Indonesia Terhadap Kesadaran Masyarakat - Istiqomah, Istiqomah (Faculty of Communications Science, Dr. Soetomo University, 2019)
As an area prone to natural disasters Aceh people should be aware of the disaster, Serambi Indonesia newspaper is expected to increase public awareness through the news, lack of awareness is feared will create panic in society. This study aims to determine whether there is influence of natural disaster reporting to public awareness in Banda Aceh city. This research uses agenda setting theory and quantitative approach with survey method and purposive sampling technique.The result of the simple linear regression analysis that there was positive influence between the news of natural disaster in daily Serambi Indonesia on public awareness of Banda Aceh and a regression coefficient of 0.590. the result of hypothesis test got t hitung was 9.670, while the value of t tabel was 1,984 at the significance level of 5%. The conclusion was that if t hitung > t tabel then Ha accepted and Ho rejected. Therefore, 9,670>1,984 then Ha is accepted. This meant that, the news of natural disasters in Daily Serambi Indonesia positively influenced and was significant to public awareness of the city of Banda Aceh.